Public Class of a Statistics Lesson Study: An Instance to Change Teachers' Beliefs - Raimundo Olfos; Soledad Estrella; Sergio Morales (Universidad Nacional, Costa Rica, 2015)
This paper presents a research on the impact of the implementation of a Statistics Lesson from the point of view of the beliefs of the teachers who observed the lesson. Eighteen teachers and seven future teachers participated in this quasi-experimental design and responded to a validated questionnaire with six propositions under a Likert scale. The questionnaire of beliefs on how to teach Statistics was applied individually to each teacher when they came to the room where public class was being delivered and it was responded as a posttest. The class observed lasted around 90 minutes. The non-parametric Wilcoxon test was used to compare the averages between the two applications. The results show slight differences, which do not become significant, on "how to teach Statistics". This research is an invitation to a further exploration and understanding of the changes of beliefs based on a public class of a lesson study as a continuous training method.